Le rose et le bleu : la fabrique du féminin et du masculin - Beauvalet-Boutouyrie, Scarlett; Berthiaud, Emmanuelle (Collection Histoire (Paris. 2013), 2016)
Une histoire de l'étude biologique, des statuts, des droits, de l'éducation, des apparences et des rôles attendus des hommes et des femmes, du XVIe au XXIe siècle, qui interroge la fabrication des concepts de masculin et de féminin.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; approches et analyses; cours; discipline; histoire; histoire et politique; postmodernisme; premier cycle; psy4910; psychologie; périodes historiques; sciences humaines; sexe/genre; stéréotypes de genre; thématiques; études de genres

Only the Literal: The Contradictions of Anti-pornography Feminism - Segal, Lynne (Sexualities, 1998)
Within feminism, battles over pornography have become the wars without end. Despite the controversy it generates, the discourses of anti-pornography feminism have continued to make inroads into legal frameworks, most recently in Canada. This piece surveys the growth and questionable appeal of such feminist campaigning, under the theoretical leadership of Catharine MacKinnon: its rewriting of feminist theory; its parasitic relation to the authoritative, phallocentric discourses of gender and sexuality; its alliance with the most reductive, behaviouristic psychology; its disavowel of fantasy and psychic life; its provocative mirroring of both the style and content of the `pornography' it deplores; its unwavering pursuit of legal remedies which enhance the power of state regulation of sexuality; its threat to subversive expressions of women's sexual agency and repudiation of any possibilities for sexual resignifications.
Keywords: cours; discipline; droits des femmes*; histoire et politique; militance; premier cycle; psychologie; ressource en ligne; sciences humaines; sex1911; sexologie; sexualité; thématiques

New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires

The social construction of heterosexuality - Wilkinson, Sue; Kitzinger, Celia (Journal of Gender Studies, 1994)
Looks at some of the key issues raised by a tradition of social constructionist work on homosexuality, focusing on the nature of heterosexuality, heterosexual self-identification and the relationship between heterosexual sexual behavior and sexual identity. Political and theorectical importance of a sustained analysis of the functions and utility of heterosexuality; Impact of social constructionist theory on research relating to lesbians and gay men.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; cours; discipline; histoire et politique; premier cycle; psychologie; périodes historiques; sciences humaines; soc2014; sociologie; thématiques